The erroneous haemoglobin-hyperlipidaemia relationship. - Nicholls, P D (1977)
Hyperlipidaemia, whether primary or secondary to parenteral feeding with intravenous lipid emulsions, causes the haemoglobin level to be erroneously high when measured spectrophotometrically. Contrary to a previous report, evidence is presented which suggests a relationship between the amount of the false rise in the haemoglobin level and the type and degree of hyperlipidaemia.